RAGE-mediated inflammation in patients with septic shock - Hofer, Stefan; Uhle, Florian; Fleming, Thomas; Schmoch, Thomas; Bruckner, Thomas; Weigand, Markus A.; Brenner, Thorsten (Journal of surgical research, 2016)
Background - The receptor for advanced glycation end-products (RAGE)-pathway is described to be a crucial component of the innate immune response in sepsis. The aims of the present study were, therefore, to delineate the kinetics of membrane-bound RAGE expression, to quantify its soluble isoforms, and to determine the extent of metabolic (e.g., AGE-CML) as well as immunologic (e.g., S100A8/A9) ligands in different inflammatory settings in humans. - Materials and methods - The presented data result from secondary analyses of an observational clinical pilot study, including patients with septic shock (n = 60), postoperative controls (n = 30), and healthy volunteers (n = 30). Surface-bound expression of RAGE by peripheral blood leukocytes was determined by flow cytometry. In addition, plasma levels of sRAGE, esRAGE, AGE-CML, S100A8/A9, S100A8/A9-CML, RBP, RBP-CML, HSA-CML, HMBG-1, and ß-Amyloid were measured using ELISA. - Results - In patients with septic shock, RAGE expression was significantly increased in comparison to both control groups, which was paralleled by a significant increase in sRAGE plasma levels. Formation of AGE-CML was shown to be dependent on the availability of the unmodified protein. However, the total amount of AGE-CML did not differ significantly between septic patients and healthy volunteers at early stages or was even lower in patients with sepsis at later stages. In contrast, immunologic ligands (e.g., S100A8/A9) were shown to be significantly elevated in septic patients within the entire study period. - Conclusions - Activation of the RAGE-pathway was shown to be of relevance in patients with septic shock, mainly driven by an increase in immunologic (e.g., S100A8/A9) rather than metabolic ligands (e.g., CML-derived AGE-formation).
Gesehen am 11.09.2019